2015
DOI: 10.1002/jmv.24323
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based study for human papillomavirus (HPV) infection in young women in Japan: A multicenter study by the Japanese human papillomavirus disease education research survey group (J‐HERS)

Abstract: A multi-center study was conducted to examine 6,628 eligible Japanese women aged from 16 to 50 years for uterine cervical abnormality and HPV infection with a liquid based-cytology test and a novel HPV test using the PCR-SSOP-Luminex(®) method identifying 31 HPV genotypes. In 3,047 normal subjects, the overall prevalence across all HPV types was 25%, while that of the common 13 high-risk (Common-13HR) types (HPV-16, 18. 31, 33, 35, 39, 45, 51, 52, 56, 58, 59, and 68) was 17%, and that of the definite high-risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 38 publications
6
51
3
Order By: Relevance
“…This study revealed low HR-HPV prevalence (5.6% overall, 4.1% in women with normal cytology) in women from a suburban area of Thailand, which was lower than that reported in population-based studies from Western countries (24.0–28.3%) (Bonde et al, 2014, Tachezy et al, 2013). Compared with other population-based studies in Asia, this HR-HPV rate was lower than reported in Japan (17%), China (21.07%), India (10.3%), Indonesia (7.9%), and Nepal (6.1%), but marginally higher than reported in Bangladesh (4.2%) (Nahar et al, 2014, Sankaranarayanan et al, 2009, Sasagawa et al, 2016, Sherpa et al, 2010, Vet et al, 2008, Wang et al, 2015). …”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…This study revealed low HR-HPV prevalence (5.6% overall, 4.1% in women with normal cytology) in women from a suburban area of Thailand, which was lower than that reported in population-based studies from Western countries (24.0–28.3%) (Bonde et al, 2014, Tachezy et al, 2013). Compared with other population-based studies in Asia, this HR-HPV rate was lower than reported in Japan (17%), China (21.07%), India (10.3%), Indonesia (7.9%), and Nepal (6.1%), but marginally higher than reported in Bangladesh (4.2%) (Nahar et al, 2014, Sankaranarayanan et al, 2009, Sasagawa et al, 2016, Sherpa et al, 2010, Vet et al, 2008, Wang et al, 2015). …”
Section: Discussioncontrasting
confidence: 75%
“…2A). HPV-52 is particularly prevalent in Asian populations (Sasagawa et al, 2016, Vet et al, 2008, Wang et al, 2015). However, the number of women with each HPV type in this study was too low to definitively confirm the most common HPV type.…”
Section: Discussionmentioning
confidence: 99%
“…All samples tested positive for β-globin, demonstrating that amplifiable DNA had been extracted from the specimens. Only high-risk HPV types were detected in the present study, namely HPV-16, -18, -31, -33, -35, -39, -45, -51, -52, -56, -58, -59 and -68 11.…”
contrasting
confidence: 52%
“…Among studies with the general female population, the reported annual incidence of any AGWs (including new and recurrent) per 100,000 population ranged between 99 among women of all ages in Germany [37] and 251 among 10- to 59-year-old women attending Pap screening in Japan [42], with a median of 224 (Table 1) [2,27,29,37-40,42,43]. The Italian prospective study [41] reported a much lower incidence compared to this range, of four cases per 100,000 females listed with GPs.…”
Section: Resultsmentioning
confidence: 99%